1979
DOI: 10.1093/nar/6.3.983
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the superhelicity on the double helix twist angle in DNA

Abstract: An attempt to estimate the relative contributions of twisting and bending to the free energy of superhelix formation from the relaxed DNA is undertaken. The extent of teritiary ordering (number of DNA axis turns tau) and that of secondary ordering (duplex twist angle beta) have been taken as thermodynamical parameters, which characterize the state of the supercoild DNA at the fixed linking number (Lk) value. Such a thermodynamical approach implies the phenomenological parameters of rigidities of twisting and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…This variance, though not very significant, may play its role in the interaction of DNA with regulatory proteins or in DNA wrapping around the nucleosome cores. The calculated values of A'I are in reasonable agreement with the other estimations of fluctuation of the -T angle based on the experimental data: &V7 =3.3-5.90 (16)(17)(18)(19)(20)(21)(22).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…This variance, though not very significant, may play its role in the interaction of DNA with regulatory proteins or in DNA wrapping around the nucleosome cores. The calculated values of A'I are in reasonable agreement with the other estimations of fluctuation of the -T angle based on the experimental data: &V7 =3.3-5.90 (16)(17)(18)(19)(20)(21)(22).…”
Section: Resultssupporting
confidence: 88%
“…In this case <(& t )t.> = N -<(,-)'> = IV .R T/9 since A tw = E& 'A and all AZN, vary independently (17). Fluctuation of the winding angle found according to the above equation: T = >= , proved to be 3.30-5.90 (16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, as the bonds of the chains of Vologodskii et a1.26 are parallel to one of the eight vectors of components f l , f l , f l , the writhing number is always the ratio of an integer to 3, as may be shown using Eq. (17), and this might introduce a systematic error.…”
Section: Radius Of Gyration and Sedimentation Constantmentioning
confidence: 99%
“…Using circular dichroism, Belintsev et al 17 have measured 3 -00 for various values of c and found 0.7 for the ratio A. The fluorescence anisotopy decay of the ethidium cation intercalated into a linear double-stranded DNA19,20 has been theoretically related to the torsional constant K of DNA.15,21 Our elementary theory15 gives a value for X between 0.8 and 1.…”
Section: Introductionmentioning
confidence: 98%